The reporting and methodological quality of systematic reviews and meta‐analyses of nursing interventions for chronic obstructive pulmonary disease ‐ A systematic review - Xiao Sun; Duo Wang; Mei Wang; Han Li; Bo Liu (Wiley, 2021)
Abstract Aims The aim of this review was to evaluate the reporting and methodological quality of systematic reviews and meta‐analyses (SRs/MAs) on nursing interventions in patients with chronic obstructive pulmonary disease (COPD) and to determine potential factors that predict high quality. Design The review is a quantitative systematic review. Data Sources PubMed, Embase and the Cochrane Database of Systematic Reviews. Review Methods A comprehensive literature search was conducted in three databases for SRs/MAs published up to 6 May 2020. The PRISMA statement and AMSTAR checklist were used to evaluate the reporting and methodological quality. Results A total of 130 articles published between 1996-2020 from 69 journals were included in this review. Multivariate regression analyses demonstrated that the following factors were related to the higher reporting quality of included articles: having a protocol or registration and being published on the Cochrane Database of Systematic Reviews. Systematic reviews including meta‐analyses, number of authors >5, number of pages and having protocol or registration were related to higher methodological quality. A strong linear correlation (r = 0.860) was detected between the scores of PRISMA and AMSTAR. Conclusion A significant number of systematic reviews and meta‐analyses on nursing interventions in patients with COPD show suboptimal reporting and poor methodology quality. The use of PRISMA and AMSTAR guidelines in conducting, reading, reviewing and editing systematic reviews and meta‐analyses is recommended to improve the quality of systematic reviews and meta‐analyses. Impact The findings of this review can provide references for health workers and health policy makers to evaluate and apply evidence‐based knowledge. Additionally, such high‐quality systematic reviews/meta‐analyses can guide medical and health practice.